2005
DOI: 10.1590/s0102-33062005000400016
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura e dinâmica da regeneração natural de uma mata de galeria no Distrito Federal, Brasil

Abstract: RESUMO -(Estrutura e dinâmica da regeneração natural de uma mata de galeria no Distrito Federal, Brasil). O objetivo deste estudo foi analisar as mudanças na estrutura e composição florística da regeneração natural na mata de galeria do Gama, localizada na Fazenda Água Limpa, no Distrito Federal, durante o período de 13 anos (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) e detectar padrões associados entre ambientes de borda e interior de mata. Foram alocadas 151 parcelas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
27

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 10 publications
3
9
1
27
Order By: Relevance
“…2) are consistent with a self-thinning pattern, as observed by Felfili (1995) and Werneck et al (2000). In a riparian forest in Distrito Federal, Oliveira & Felfili (2005) recorded intense reduction in total density and increase in basal area; they suggested that greater shading of the area would hinder the growth of heliophilous species. This could also be happening in our study area, since all species that (Ratter et al 1973;Pott & Pott 1994;Oliveira-Filho & Ratter 1995;IBGE 2002;Durigan et al 2004;Mendonça et al 2008).…”
Section: Resultssupporting
confidence: 78%
“…2) are consistent with a self-thinning pattern, as observed by Felfili (1995) and Werneck et al (2000). In a riparian forest in Distrito Federal, Oliveira & Felfili (2005) recorded intense reduction in total density and increase in basal area; they suggested that greater shading of the area would hinder the growth of heliophilous species. This could also be happening in our study area, since all species that (Ratter et al 1973;Pott & Pott 1994;Oliveira-Filho & Ratter 1995;IBGE 2002;Durigan et al 2004;Mendonça et al 2008).…”
Section: Resultssupporting
confidence: 78%
“…The lower section turned out to be the most differentiated community (Marimon et al, 2001(Marimon et al, , 2002, leading to a particular set of species (trees and seedlings) with peculiar establishment strategies linked especially to a humidity gradient. These findings agree with those of Oliveira & Felfili (2005) studies of natural regeneration of a gallery forest in Central Brazil.…”
Section: Regeneration Categories and Environmental Gradientssupporting
confidence: 92%
“…As espécies com maior número de indivíduos amostrados na área de referência são tolerantes à sombra, enquanto na área em restauração elas se distribuem entre tolerantes e intolerantes, indicando que a comunidade em restauração encontra-se em etapa sucessional intermediária. Como observado por Oliveira & Felfili (2005), em mata de galeria no Distrito Federal, durante a sucessão há o fechamento gradual do dossel, que resulta em elevação da mortalidade de espécies que necessitam de luz e aumento nas populações de espécies tolerantes à sombra.…”
Section: Discussionunclassified